Blockchain for Child Labour Decrease - Senou, Rosaire Brice; Dégila, Jules; Adjobo, Esther Chabi; Djossou, Abigail Priscilla M. (Elsevier, 2019)
The blockchain technology impacts the supply chain and allows the creation of smart contract. This contract is executed digitally and securely without the presence of a middleman when all requirements are met. West and Central Africa countries produce 70% of world's cocoa, while child labour is an issue as millions of children work in that sector. This paper contribution is mainly to enlighten smart contract adoption with respect to child abuse and to contribute to strategies for child labour reduction.
As Internet grows, new technologies are emerging and changing significantly the ways people interact with their environment, how businesses are conducted and the evolution of the economy. One such disruptive technology is the “blockchain” (United Nations, 2017). Indeed, blockchain is a technology that allows a decentralized environment to be created for the executions of transactions without any means of data alteration (Holotescu, 2018).
Keywords: blockchain; smart contract; west and central Africa; cocoa; child labour